Evaluation of the safety criteria of Brazilian Standard NBR 6118 for slender members based on reliability analyses - Stucchi, F. R. [UNESP]; Santos, S. H. C.; Franco, R. M.; Faber, M. H.; Kohler, J.; Nishijima, K. (Crc Press-taylor & Francis Group, 2011)
The Brazilian Standard for concrete design defines its safety criteria in a deterministic way, through partial safety factors. However, it is nowadays recognized that a rational basis for the evaluation of the structural safety is only achieved through complete probabilistic analyses. An alternative to the application of these highly complex methods is the definition, after an optimization process, of safety factors that could assure to a structure designed deterministically, an adequate safety level when evaluated through reliability analyses (the so called code calibration process). One of the issues for defining these safety factors is the influence of geometric deviations in slender members, such as slabs and columns. These deviations include the variations in the member thicknesses and in the concrete cover. Some selected reliability analyzes of slender elements are presented herein. It is shown that some changes in the Brazilian Standard are necessary for attaining more acceptable levels of safety.